2015
DOI: 10.1177/0040517515612364
|View full text |Cite
|
Sign up to set email alerts
|

Consistency and reliability of untrained consumers' perceptions of fabric hand of men's suiting

Abstract: The current study is aimed to analyze the consistency and reliability of untrained consumers' perception of fabric hand. A group of untrained assessors are recruited to evaluate the fabric hand of a number of suit fabrics through free sorting and rating experiments. Two statistical methods have been used to measure the consistency between the sorting and rating data of the assessors in replicated sessions. According to the types of data obtained from different evaluation procedures, different multidimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Tactile sensation can also be investigated by wearable tactile sensors, artificial fingers or subjective sensory tests. 7,10,14,20–24 Considering the number of trials required, the investigation of tactile comfort by trained or untrained participants via sensory tests is more time consuming and difficult when compared to objective measurements, yet subjective evaluation of tactile comfort is quite common and essential for scientific researches. Bertaux et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tactile sensation can also be investigated by wearable tactile sensors, artificial fingers or subjective sensory tests. 7,10,14,20–24 Considering the number of trials required, the investigation of tactile comfort by trained or untrained participants via sensory tests is more time consuming and difficult when compared to objective measurements, yet subjective evaluation of tactile comfort is quite common and essential for scientific researches. Bertaux et al.…”
mentioning
confidence: 99%
“…Xue et al. 23 analyzed the consistency and reliability of untrained consumers' perception of fabric hand. It was reported that simple sorting and rating procedures are both efficient methods for acquiring consistent sensory results from untrained assessors on a relatively large number of textile products.…”
mentioning
confidence: 99%
“…6,7 Statistical (or classical) methods are capable of solving many modeling problems due to their good capacity of identifying linear patterns embedded in different information sources and then finding correlations between different datasets or attributes from a large quantity of numerical data. Commonly used statistical methods include principle component analysis (PCA), 8,9 multiple factor analysis, 10 multidimensional scaling, [11][12][13] linear regression analysis, 14,15 and various types of correlation coefficient analysis. 16,17 However, they also have drawbacks.…”
mentioning
confidence: 99%